Forwarding Address Unknown William Forsythe and Frankfurt - Nugent, Ann (Dance Books Ltd., Alton,Hampshire (UK), 2003)
Review of William Forsythe and Frankfurt. [N.N.N.N.] turns out to be a spoof, a witty exploitation of how a seemingly simple idea can have endless computations. It is the present, more than the past or the future, that matters to Forsythe. PALABRAS CLAVE: William Forsythe, Ballett Frankfurt, [N.N.N.N.], Quintett, Vile Parody of Address.